2014
DOI: 10.1002/ar.22775
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Morphological Variation of Extant Sloth Skulls and their Implication for Future Conservation Efforts

Abstract: Several studies have shown an increased morphological variability of sloths from mammalian norms, affecting varied phenotypic traits from skeletal parts to soft tissues. We present here the first descriptive comparison of the whole skull morphology within the two extant sloth genera, combining geometric morphometric approaches with comparative anatomy. We used these methods to explore the patterns of the intra‐ and interspecific morphological variation of the skull with regard to several factors such as phylog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…Whereas this is often due to the limitations of the available material, it makes it difficult to account for intraspecific variation, to distinguish between species level distinctions and sexual dimorphism ( McDonald, 2006 ), or to assess the reliability of systematic characters based on fossil taxa. The present study, like other recent detailed analyses of xenarthran skull morphology ( Wible & Gaudin, 2004 ; Gaudin, 2011 ; McAfee & Naples, 2012 ; De Iuliis et al, 2014 ; Hautier et al, 2014 ; Gaudin et al, 2015 ), has revealed substantial variation in a variety of cranial features in Holmesina floridanus . These features include the number, size and/or position of a variety of cranial foramina (anterior palatal foramen, maxillary foramen, minor palatine foramina, foramen for frontal diploc vein, ethmoid foramen, transverse canal foramen, foramina for rami temporalis, suprameatal foramen, hypoglossal foramen); the presence, size and shape of various processes (anteroventral process on premaxilla, lacrimal tubercle, ventral zygomatic process, postorbital process of jugal, orbito-auricularis crest, medial pterygoid process, circular boss on lateral wall of promontorium, medial shelf of petrosal, coronoid process of mandible) or depressions (digastric fossa, tensor tympani fossa, fossa incudis); and the shape of other cranial (proportions of nasal bone, shape of anterior margin of premaxilla, shape of naso-frontal and jugal/squamosal sutures, shape of external nares and occipital exposure of mastoid) or dental features (e.g., outline of M4 and M5, shape of wear facets on M1).…”
Section: Discussionsupporting
confidence: 80%
“…Whereas this is often due to the limitations of the available material, it makes it difficult to account for intraspecific variation, to distinguish between species level distinctions and sexual dimorphism ( McDonald, 2006 ), or to assess the reliability of systematic characters based on fossil taxa. The present study, like other recent detailed analyses of xenarthran skull morphology ( Wible & Gaudin, 2004 ; Gaudin, 2011 ; McAfee & Naples, 2012 ; De Iuliis et al, 2014 ; Hautier et al, 2014 ; Gaudin et al, 2015 ), has revealed substantial variation in a variety of cranial features in Holmesina floridanus . These features include the number, size and/or position of a variety of cranial foramina (anterior palatal foramen, maxillary foramen, minor palatine foramina, foramen for frontal diploc vein, ethmoid foramen, transverse canal foramen, foramina for rami temporalis, suprameatal foramen, hypoglossal foramen); the presence, size and shape of various processes (anteroventral process on premaxilla, lacrimal tubercle, ventral zygomatic process, postorbital process of jugal, orbito-auricularis crest, medial pterygoid process, circular boss on lateral wall of promontorium, medial shelf of petrosal, coronoid process of mandible) or depressions (digastric fossa, tensor tympani fossa, fossa incudis); and the shape of other cranial (proportions of nasal bone, shape of anterior margin of premaxilla, shape of naso-frontal and jugal/squamosal sutures, shape of external nares and occipital exposure of mastoid) or dental features (e.g., outline of M4 and M5, shape of wear facets on M1).…”
Section: Discussionsupporting
confidence: 80%
“…Only one extant genus is absent from our data set, the poorly known greater fairy armadillo Calyptophractus . Species identification for extant specimens was based on collection data, geographical origin, and cranial anatomy (de Moraes‐Barros, Silva, & Morgante, ; Hautier, Billet, Eastwood, & Lane, ; Wetzel, ). Skulls were scanned by micro‐computed tomography (µCT) on X‐ray platforms at the Museum national d'Histoire naturelle (France) in Paris (AST‐RX platform); the Department of Engineering of the University of Cambridge (United Kingdom); the Steinmann Institut, University of Bonn (Germany); and the University of Montpellier (France).…”
Section: Methodsmentioning
confidence: 99%
“…A total of 25 unsexed sloth foetuses were examined, representing four species of both extant genera: Bradypus tridactylus , Bradypus variegatus , Choloepus didactylus , and Choloepus hoffmanni 51 . Species identification was based on collection data (especially geographical origin) and cranial anatomy 51 52 and was possible for 17 of our 25 specimens ( S2 ). They range in size from 70 to 200 mm crown rump length (CRL), measured from the vertex of the skull to the base of the tail.…”
Section: Methodsmentioning
confidence: 99%